A method for manufacturing a vertical axis wind turbine and a vertical axis wind turbine
Patent Information
- Application Number
- CN202611179552.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-09
AI Technical Summary
[0003]然而,目前的垂直轴风力发电机在作业过程中存在较高的机械摩擦损失以及空气阻力,使得能量转换效率较低
[0017]这样,通过分别对轴承组件和叶片进行针对性的涂层制备,在轴承表面形成包含二硫化钼、二氧化硅纳米颗粒和聚酰亚胺的复合超滑涂层,在叶片表面形成包含二硫化钼和二氧化硅的复合超滑涂层,轴承超滑涂层利用二硫化钼的层状低剪切结构提供优异润滑性能,同时二氧化硅纳米颗粒作为硬质填料提高涂层的耐磨性和硬度,聚酰亚胺作为粘合剂确保涂层各组分之间及涂层与轴承基材之间的牢固结合,使轴承表面摩擦系数从0.12大幅降至0.03,减少约75%的机械摩擦损耗,从而降低风机的启动风速,使其在微风条件下即可启动运行;叶片超滑涂层利用二硫化钼的低表面能特性降低叶片表面与气流之间的粘性阻力,配合二氧化硅纳米颗粒对涂层致密度和硬度的进一步提升,使叶片阻力系数从0.45降至0.30,减少约33%的空气阻力,显著提升了气动效率。并且,轴承涂层和叶片涂层的制备相互独立且并行进行,两条涂层产线可同时开工,互不制约,大幅缩短了整体制造周期,提高了生产效率,适合工业化批量生产。最终,轴承组件和叶片各自完成超滑涂层制备后统一总装,机械摩擦损耗和空气动力阻力的协同降低使得整机在不同风速条件下的发电效率均获得显著提升,其中在3-5 m/s的低风速条件下发电量提升尤为显著,可达50%,6-10 m/s的中风速下提升约40%,11-15 m/s的高风速下提升约30%,平均功率输出整体提升约40%,使得能量转换效率显著提升。
Smart Images

Figure CN122879702A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of wind power generation technology, and more specifically, to a method for manufacturing a vertical axis wind turbine and the vertical axis wind turbine itself. Background Technology
[0002] As a wind energy capture device, vertical axis wind turbines have demonstrated significant application potential in a variety of environments due to their unique structural design. Compared with traditional horizontal axis wind turbines, vertical axis wind turbines have advantages such as compact structure, lower noise emissions, and insensitivity to changes in wind direction, making them particularly suitable for urban environments, building surfaces, and areas with variable wind directions or limited space.
[0003] However, current vertical axis wind turbines suffer from high mechanical friction losses and air resistance during operation, resulting in low energy conversion efficiency.
[0004] In summary, how to reduce mechanical friction loss and air resistance in vertical axis wind turbines and improve energy conversion efficiency is a problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0005] In view of this, the purpose of this application is to provide a method for manufacturing a vertical axis wind turbine and a vertical axis wind turbine, thereby reducing mechanical friction loss and air resistance of the vertical axis wind turbine and improving energy conversion efficiency.
[0006] To achieve the above objectives, this application provides the following technical solution: A method for manufacturing a vertical axis wind turbine, the vertical axis wind turbine comprising a bearing assembly and blades, the method comprising: S100, pretreating the surface of the substrate of the bearing assembly and preparing a bearing super-lubricating coating; S200, pretreating the surface of the substrate of the blade and preparing a blade super-lubricating coating; S300, assembling the bearing assembly with the prepared bearing super-lubricating coating and the blade with the prepared blade super-lubricating coating into the complete vertical axis wind turbine; the bearing super-lubricating coating comprises molybdenum disulfide as a substrate material, silica nanoparticles as nanofillers, and a binder. Polyimide; S100 specifically includes: S110, sequentially cleaning and surface-activating the surface of the substrate of the bearing assembly; S120, depositing the bearing super-lubricating coating on the surface of the substrate of the bearing assembly using a chemical vapor deposition process; the blade super-lubricating coating includes molybdenum disulfide and silicon dioxide; S200 specifically includes: S210, sequentially cleaning and surface-activating the surface of the substrate of the blade; S220, depositing the blade super-lubricating coating on the surface of the substrate of the blade using a physical vapor deposition process; wherein, S100 and S200 are performed independently and in parallel.
[0007] In some embodiments, in S120, the process conditions for the chemical vapor deposition process are: deposition temperature: 400°C; chamber pressure: 10... - ³ Torr; Flow rate of the precursor mixture of molybdenum disulfide and silicon dioxide: 20 sccm; Deposition time: 30 min-90 min; Thickness of the bearing super-lubricating coating: 50 nm-100 nm.
[0008] In some embodiments, in step S120, the deposition time in the chemical vapor deposition process is 60 min, and the thickness of the bearing super-lubricating coating is 50 nm.
[0009] In some embodiments, step S110 specifically includes: S111, using an ultrasonic cleaner with anhydrous ethanol as solvent, cleaning the substrate surface of the bearing assembly at 40°C for 30 minutes; S112, using a plasma treatment device to activate the cleaned substrate surface of the bearing assembly in an oxygen atmosphere, with a treatment power of 50W and a treatment time of 5 minutes.
[0010] In some embodiments, in step S220, the process conditions of the physical vapor deposition process are as follows: deposition temperature is 150°C; working gas is high-purity argon, and the gas pressure is maintained at 0.3 Pa; sputtering power is 80 W; deposition time is 60 min; and the thickness of the blade super-lubricating coating is 20 nm to 40 nm.
[0011] In some embodiments, in step S220, the thickness of the blade super-lubricating coating is 30 nm.
[0012] In some embodiments, step S210 specifically includes: S211, using an ultrasonic cleaner with acetone as solvent, cleaning the substrate surface of the blade at 30°C for 20 minutes; S212, using ultraviolet light irradiation technology, modifying the substrate surface of the cleaned blade under nitrogen protection for 15 minutes.
[0013] In some embodiments, step S300 further includes: installing the bearing assembly coated with the super-slippery coating between the hub and the central main shaft of the vertical axis wind turbine, and adjusting the bearing clearance; fixing the blade coated with the super-slippery coating to the circumference of the hub with high-strength bolts, and adjusting the blade angle to a preset windward posture; after the assembly is completed, starting the vertical axis wind turbine to perform no-load operation test and load operation test, and recording the power generation performance data.
[0014] A vertical axis wind turbine generator, manufactured using the method described above, includes a bearing assembly, blades, a support, and a base.
[0015] In some embodiments, the bearing assembly is a high-performance metal alloy, the bearing assembly is machined and polished, and its surface roughness Ra≤0.05 micrometers; the blade is a carbon fiber reinforced epoxy resin composite material, the blade is formed by autoclave process, its surface is polished to a mirror effect, and the outer surface of the blade is provided with biomimetic microstructures.
[0016] This application provides a method for manufacturing a vertical axis wind turbine, which includes a bearing assembly and blades. The method includes pretreating the surface of the bearing assembly substrate and preparing a bearing super-lubricating coating, and pretreating the surface of the blade substrate and preparing a blade super-lubricating coating. The bearing assembly with the bearing super-lubricating coating and the blade with the blade super-lubricating coating are then assembled into the vertical axis wind turbine. The bearing super-lubricating coating comprises molybdenum disulfide as a substrate material, silica nanoparticles as nanofillers, and polyimide as a binder. The pretreating of the bearing assembly substrate surface and preparation of the bearing super-lubricating coating specifically includes sequentially cleaning and surface-activating the bearing assembly substrate surface, and depositing the bearing super-lubricating coating on the bearing assembly substrate surface using a chemical vapor deposition process. The blade super-lubricating coating comprises molybdenum disulfide and silica. The pretreating of the blade substrate surface and preparation of the blade super-lubricating coating specifically includes sequentially cleaning and surface-activating the blade substrate surface, and depositing the blade super-lubricating coating on the blade substrate surface using a physical vapor deposition process. Furthermore, the preparation of the bearing superlubricating coating and the blade superlubricating coating are carried out independently and in parallel.
[0017] In this way, by selectively preparing coatings for the bearing assembly and blades, a composite super-lubricating coating containing molybdenum disulfide, silica nanoparticles, and polyimide is formed on the bearing surface, and a composite super-lubricating coating containing molybdenum disulfide and silica is formed on the blade surface. The bearing super-lubricating coating utilizes the layered low-shear structure of molybdenum disulfide to provide excellent lubrication performance, while silica nanoparticles act as hard fillers to improve the wear resistance and hardness of the coating. Polyimide acts as a binder to ensure a strong bond between the components of the coating and between the coating and the bearing substrate. This significantly reduces the bearing surface friction coefficient from 0.12 to 0.03, reducing mechanical friction loss by approximately 75%, thereby lowering the wind turbine's starting wind speed and enabling it to start operating under light wind conditions. The blade super-lubricating coating utilizes the low surface energy characteristics of molybdenum disulfide to reduce the viscous resistance between the blade surface and the airflow. Combined with the further enhancement of coating density and hardness by silica nanoparticles, the blade drag coefficient is reduced from 0.45 to 0.30, reducing air resistance by approximately 33% and significantly improving aerodynamic efficiency. Furthermore, the preparation of bearing coatings and blade coatings is carried out independently and in parallel. The two coating production lines can operate simultaneously without interfering with each other, significantly shortening the overall manufacturing cycle, improving production efficiency, and making them suitable for industrial mass production. Finally, after the bearing assembly and blades have completed their respective super-lubricating coating preparations, they are assembled together. The synergistic reduction in mechanical friction loss and aerodynamic drag significantly improves the power generation efficiency of the entire unit under different wind speed conditions. The power generation increase is particularly significant at low wind speeds of 3-5 m / s, reaching up to 50%; at medium wind speeds of 6-10 m / s, it increases by about 40%; and at high wind speeds of 11-15 m / s, it increases by about 30%. The overall average power output increases by about 40%, resulting in a significant improvement in energy conversion efficiency. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of this application or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of this application. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0019] Figure 1 This is a schematic flowchart illustrating the manufacturing method of a vertical axis wind turbine provided in an embodiment of this application. Detailed Implementation
[0020] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0021] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. The terminology used in the following embodiments is for the purpose of describing specific embodiments only and is not intended to be a limitation of this application. As used in the specification and appended claims of this application, the singular expressions "a," "an," "the," "the," "the," and "this" are intended to also include expressions such as "one or more," unless the context clearly indicates otherwise. It should also be understood that in the embodiments of this application, "one or more" refers to one, two, or more; "and / or" describes the relationship between related objects, indicating that three relationships may exist; for example, A and / or B can represent: A alone, A and B simultaneously, or B alone, where A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects are in an "or" relationship.
[0022] References to "one embodiment" or "some embodiments" as described in this specification mean that one or more embodiments of this application include a specific feature, structure, or characteristic described in connection with that embodiment. Therefore, the phrases "in one embodiment," "in some embodiments," "in other embodiments," "in still other embodiments," etc., appearing in different parts of this specification do not necessarily refer to the same embodiment, but rather mean "one or more, but not all, embodiments," unless otherwise specifically emphasized. The terms "comprising," "including," "having," and variations thereof mean "including but not limited to," unless otherwise specifically emphasized.
[0023] This application provides a method for manufacturing a vertical axis wind turbine, which includes a bearing assembly and blades. The manufacturing method includes: S100. Pre-treat the surface of the substrate of the bearing assembly and prepare a super-lubricating coating for the bearing.
[0024] S110. The substrate surface of the bearing assembly is cleaned and surface activated in sequence.
[0025] S111. Using an ultrasonic cleaner with anhydrous ethanol as solvent, clean the surface of the bearing assembly substrate for 30 minutes at 40°C to remove surface grease and impurities.
[0026] S112. Using plasma treatment equipment, the surface of the substrate of the cleaned bearing assembly is activated in an oxygen atmosphere. The treatment power is 50W and the treatment time is 5 minutes to improve the adhesion between the subsequent coating and the substrate.
[0027] S120. A bearing super-lubricating coating is deposited on the substrate surface of the bearing assembly using a chemical vapor deposition (CVD) process. The bearing super-lubricating coating includes molybdenum disulfide (MoS2) as the substrate material, silica (SiO2) nanoparticles as nanofillers, and polyimide (PI) as a binder.
[0028] The process conditions for chemical vapor deposition are as follows: deposition temperature 400℃; chamber pressure 10... - ³Torr; the flow rate of the precursor mixture of molybdenum disulfide and silicon dioxide was 20 sccm; the deposition time was 30 min-90 min; and the thickness of the bearing super-lubricating coating was 50 nm-100 nm.
[0029] Optionally, the deposition time is 60 min and the thickness of the bearing super-lubricating coating is 50 nm.
[0030] By forming a composite super-lubricating coating containing molybdenum disulfide, silica nanoparticles, and polyimide on the surface of a bearing assembly substrate, the layered low-shear structure of molybdenum disulfide provides excellent lubrication performance, silica nanoparticles serve as hard fillers to improve the hardness and wear resistance of the coating, and polyimide acts as a binder to ensure a strong bond between the components of the coating and between the coating and the bearing substrate.
[0031] Friction coefficient measurements verified that the average friction coefficient of the untreated bearing was 0.12, while that after applying the super-lubricating coating, it dropped to 0.03, reducing mechanical friction loss by approximately 75%. The lower friction coefficient allows the fan to overcome static friction and start operating at lower wind speeds, while also reducing energy loss during operation and improving overall mechanical efficiency.
[0032] Meanwhile, the cleaning and plasma activation treatment in step S110 effectively removes oil and impurities from the surface of the bearing substrate, and increases the surface energy of the substrate by oxygen plasma bombardment, which significantly enhances the bonding strength between the super-slippery coating and the metal substrate, preventing the coating from peeling off and failing during long-term rotational friction.
[0033] S200. Pre-treat the surface of the substrate of the blade and prepare a super-lubricating coating for the blade.
[0034] S210. The substrate surface of the blade is cleaned and surface activated in sequence.
[0035] S211. Use an ultrasonic cleaner with acetone as the solvent to clean the surface of the blade substrate for 20 minutes at 30°C to ensure the surface is clean and dust-free.
[0036] S212. Using ultraviolet light irradiation technology, the substrate surface of the cleaned blade is modified under nitrogen protection for 15 minutes to enhance the adhesion of the coating.
[0037] S220 employs physical vapor deposition (PVD) to deposit a super-lubricating coating on the substrate surface of the blade. The super-lubricating coating comprises molybdenum disulfide and silicon dioxide. The PVD process conditions are: deposition temperature 150℃; working gas is high-purity argon, maintained at 0.3 Pa; sputtering power is 80 W; deposition time is 60 min; and the thickness of the super-lubricating coating is 20 nm–40 nm.
[0038] Optionally, the thickness of the super-lubricating coating on the blade is 30 nm.
[0039] By forming a composite super-lubricating coating containing molybdenum disulfide and silica on the surface of the blade substrate, the low surface energy of molybdenum disulfide is used to reduce the viscous drag between the blade surface and the airflow. Combined with the increased density and hardness of the coating due to silica nanoparticles, the air resistance on the blade surface is effectively reduced. Wind tunnel experiments verified that, within the wind speed range of 5-15 m / s, the drag coefficient of the uncoated blade is approximately 0.45, while that of the blade coated with the super-lubricating coating drops to 0.30, reducing air resistance by approximately 33% and significantly improving aerodynamic efficiency and energy capture efficiency.
[0040] Meanwhile, the cleaning and ultraviolet modification treatment in step S210 removes the release agent and contaminants from the surface of the blade substrate by ultrasonic cleaning with acetone, and performs photochemical modification on the surface of carbon fiber reinforced plastic by ultraviolet irradiation under nitrogen protection, increasing the surface polar groups, thereby improving the adhesion between the blade super-slip coating and the composite material substrate, and ensuring the long-term stability of the coating under high-speed airflow.
[0041] It should be noted that steps S100 and S200 are independent and run in parallel. The two coating production lines can start up at the same time without restricting each other. Each line selects the optimal deposition process to process the coatings separately, which greatly shortens the overall manufacturing cycle, improves production efficiency, is suitable for industrial mass production, and reduces manufacturing costs.
[0042] S300. Assemble the bearing assembly with the bearing super-lubricating coating and the blade with the blade super-lubricating coating into the vertical axis wind turbine generator.
[0043] The bearing assembly coated with a super-lubricating coating is installed between the hub and the central shaft of the vertical axis wind turbine. The bearing clearance is adjusted to ensure smooth rotation and good sealing. A small amount of solid lubricant is added to reduce frictional resistance during initial operation.
[0044] Blades coated with a super-slippery coating are fixed to the hub circumferentially with high-strength bolts, and the angle of each blade is adjusted to a preset windward orientation using precision gauges to improve energy capture efficiency.
[0045] After all components are installed, a comprehensive inspection is carried out to confirm that all components are securely connected and operate smoothly. The vertical axis wind turbine is then started to conduct no-load and load operation tests, and performance data such as bearing speed, temperature, power generation efficiency, and output power are recorded.
[0046] After the bearing assembly and blades have completed their respective super-lubricating coating preparations, they are assembled together. The bearing coated with the super-lubricating coating reduces the rotational friction loss between the hub and the central main shaft, while the blade coated with the super-lubricating coating reduces the aerodynamic drag on the blade surface. The synergistic effect of the two significantly improves the overall energy conversion efficiency of the vertical axis wind turbine.
[0047] Through long-term monitoring of actual wind field environments, and continuous recording for one month within a typical wind speed range (3-8 m / s), the average power output of vertical axis wind turbines coated with super-slippery coatings increased by about 40%, especially under low wind speed (3-5 m / s) conditions, the power generation increased by 50%.
[0048] Meanwhile, the super-slip coating reduces mechanical wear and enhances surface corrosion resistance, extending the service life of bearings and blades by approximately 30%, reducing maintenance frequency and costs, and improving the long-term stability of the system.
[0049] In addition, the mechanical precision and aerodynamic optimization of the system were ensured by adjusting the bearing clearance and calibrating the blade angle, while no-load and load tests verified the system's reliability and power generation performance.
[0050] The vertical axis wind turbine prepared in this application is particularly suitable for application scenarios with low wind speed and complex turbulence, such as building surface installations in urban environments. It effectively solves the problem of low efficiency of traditional vertical axis wind turbines under low wind speed conditions and significantly improves the energy conversion efficiency of vertical axis wind turbines.
[0051] Example 1
[0052] This embodiment provides a specific preparation method for a bearing super-lubricating coating and a blade super-lubricating coating, and tests and verifies their performance.
[0053] 1. Preparation of bearing substrate
[0054] The bearing body is made of a high-performance metal alloy—chromium-molybdenum-vanadium steel (CrMoV). The outer diameter and inner bore of the bearing are precision-machined using CNC machine tools to ensure dimensional accuracy of ±0.005 mm. Multi-stage grinding and polishing processes are employed to achieve a surface roughness Ra ≤ 0.05 micrometers on both the inner and outer surfaces, ensuring coating adhesion quality. After carburizing and quenching, the surface hardness is increased to HRC60 or higher while maintaining core toughness.
[0055] 2. Preparation of blade substrate
[0056] The blades are made of carbon fiber reinforced epoxy resin composite material (CFRP) with high modulus carbon fiber (E-Modulus) having a tensile strength ≥7 GPa and an elastic modulus ≥230 GPa.
[0057] The blades are manufactured by stacking and pressing multiple layers of prepreg in an autoclave to ensure the consistency and reliability of the overall blade structure. The finished blades are then ground and polished to achieve a mirror finish.
[0058] 3. Preparation of super-lubricating coating on bearing surface
[0059] Using an ultrasonic cleaner with anhydrous ethanol as the solvent, the bearing surface was cleaned for 30 minutes at 40°C to remove grease and impurities.
[0060] A plasma treatment device was used to activate the bearing surface in an oxygen atmosphere. The power was set to 50W and the treatment time was 5 minutes to improve the coating adhesion.
[0061] Superlubricating coatings for bearings were prepared using chemical vapor deposition (CVD): The treated bearing was placed in a vacuum CVD reaction chamber, and the temperature was gradually increased to 400°C while maintaining the chamber pressure at 10. - ³Torr; A mixture of MoS2, SiO2 precursor gas, and polyimide (PI) solution is introduced at a flow rate of 20 sccm and deposited continuously for 60 min to form a uniform, dense, and ultra-slippery coating with a thickness precisely controlled at 50 nanometers. After natural cooling to room temperature, the coating is removed to ensure structural stability.
[0062] Optionally, platinum (Pt) nanoparticles are also introduced as a catalyst during the CVD deposition process. The average particle size of the platinum nanoparticles is 5 nanometers, which can promote the reaction rate during the CVD process and improve the deposition efficiency.
[0063] 4. Preparation of super-lubricating coating on blade surface
[0064] Using an ultrasonic cleaner with acetone as the solvent, the blade surface was cleaned at 30°C for 20 minutes to ensure it was clean and dust-free. Ultraviolet light irradiation was then applied to the blade surface under nitrogen protection for 15 minutes to modify the coating adhesion.
[0065] A super-lubricating coating was prepared on the blade using physical vapor deposition (PVD): the blade was fixed in a magnetron sputtering apparatus, the substrate temperature was set to 150℃, the working gas was high-purity argon, and the pressure was maintained at 0.3 Pa. MoS2 and SiO2 were selected as the target materials, the total sputtering power was 80 W, the duration was 60 min, and the coating thickness was controlled to 30 nm. The uniformity and coverage of the coating were inspected using an optical microscope to ensure that there were no defects.
[0066] 5. Performance Testing
[0067] 5.1 Measurement of friction coefficient
[0068] The effectiveness of the super-lubricating coating was verified by measuring the coefficient of friction of the bearing surfaces before and after coating using specialized instruments. The results showed that the average coefficient of friction of the untreated bearing was 0.12, while it decreased to 0.03 after coating with the super-lubricating coating.
[0069] 5.2 Air Resistance Test
[0070] The change in air drag of blades after coating with a super-lubricating coating was evaluated through wind tunnel experiments. In the wind speed range of 5-15 m / s, the drag coefficient of the uncoated blade was approximately 0.45, while that of the coated blade decreased to 0.30.
[0071] Example 2
[0072] This embodiment sets different coating thickness gradients and observes the effect of coating thickness on friction coefficient and air resistance to determine the optimal thickness parameters.
[0073] 1. Bearing super-lubricating coating thickness gradient experiment
[0074] Using the same CVD process as in Example 1, three groups of samples with bearing coating thicknesses of 30 nm, 50 nm, and 70 nm were prepared. The coefficient of friction of each group of samples was measured under the same test conditions.
[0075] Table 1. Friction coefficients for different bearing coating thicknesses
[0076] As shown in Table 1, the coefficient of friction gradually decreases as the bearing coating thickness increases from 30 nm to 50 nm; however, the coefficient of friction rebounds when the thickness is further increased to 70 nm.
[0077] The lowest coefficient of friction, 0.03, can be obtained when the bearing coating thickness is 50nm.
[0078] 2. Experiment on thickness gradient of super-lubricating coating on blades
[0079] Using the same PVD process as in Example 1, three groups of samples with blade coating thicknesses of 20 nm, 30 nm, and 40 nm were prepared. Under the same test conditions and wind speeds ranging from 5 to 15 m / s, the drag coefficients of each group of samples were measured.
[0080] Table 2 Drag coefficients for different blade coating thicknesses
[0081] As shown in Table 2, the blade drag coefficient is lowest at a coating thickness of 30 nm, which is 0.30. When the coating thickness is 20 nm, the coverage is not complete, and the drag reduction effect is insufficient; when the thickness is 40 nm, the drag coefficient rebounds somewhat.
[0082] Based on the experimental results of the combined bearing and blade coating thickness gradient, the combination of 50nm bearing coating and 30nm blade coating is the globally optimal solution.
[0083] Example 3
[0084] This embodiment evaluates the improvement in the overall power generation efficiency of a vertical axis wind turbine after applying a super-slippery coating under different wind speed conditions.
[0085] Vertical axis wind turbines prepared in Example 1, coated with a bearing super-lubricating coating (CVD process, 50 nm thickness) and a blade super-lubricating coating (PVD process, 30 nm thickness), were used to monitor their power generation efficiency over a long period in a real wind farm environment. Three typical wind speed ranges—low wind speed (3-5 m / s), medium wind speed (6-10 m / s), and high wind speed (11-15 m / s)—were selected, and the power generation in each range was continuously recorded and compared with that of a conventional vertical axis wind turbine without the super-lubricating coating.
[0086] Table 3 Power Boost Ratio in Different Wind Speed Ranges
[0087] As shown in Table 3, the power generation is most significantly improved under low wind speed conditions, with an average power output increase of about 50%, indicating that the super-slippery coating effectively reduces mechanical friction and air resistance losses at startup wind speed and low wind speed.
[0088] Under medium wind speed conditions, power generation efficiency steadily improves, with average power output increasing by approximately 40%.
[0089] Under high wind speed conditions, although the increase is relatively small, the system stability is enhanced, the power generation still increases, and the average power output increases by about 30%.
[0090] Furthermore, by optimizing the airflow path through computational fluid dynamics (CFD) simulation, energy capture efficiency is further improved, especially under low wind speed conditions.
[0091] In summary, the vertical axis wind turbine coated with the super-slippery coating showed a significant improvement in power generation efficiency throughout the entire test wind speed range, especially under low wind speed conditions. This proves that the vertical axis wind turbine manufacturing method provided in this application effectively solves the technical problem of low efficiency of traditional vertical axis wind turbines under low wind speed conditions.
[0092] Comparative Example
[0093] 1. Experimental Setup
[0094] Under the same experimental conditions (wind speed range 5-15m / s, temperature 20℃, humidity 60%, continuous operation for one month), the following two groups of objects were compared and tested: Experimental group: Vertical axis wind turbine system coated with super-slippery coating (bearing coating CVD process 50nm, blade coating PVD process 30nm).
[0095] Control group: Conventional vertical axis wind turbine system without super-slip coating.
[0096] 2. Comparison of Experimental Results
[0097] 2.1 Comparison of friction coefficients
[0098] Table 4 Comparison of Friction Coefficients
[0099] As shown in Table 4, the super-slippery coating significantly reduces the friction coefficient of the bearing surface, reduces mechanical loss, and improves the mechanical efficiency of the system.
[0100] 2.2 Comparison of Air Resistance
[0101] Table 5 Comparison of Air Resistance
[0102] As shown in Table 5, the super-slippery coating effectively optimizes the airflow path, significantly reduces air resistance, and improves energy capture efficiency.
[0103] 2.3 Comparison of power generation efficiency
[0104] Table 6 Comparison of Power Generation Efficiency
[0105] As shown in Table 6, the power generation efficiency of the super-slippery coating VAWT is significantly improved under different wind speed conditions, especially in low wind speed environments.
[0106] Comparative experiments clearly demonstrate that, under identical environmental conditions and testing methods, the vertical axis wind turbine coated with a super-lubricating coating significantly outperforms the traditional vertical axis wind turbine without such a coating in three key indicators: friction coefficient, air resistance, and power generation efficiency. This proves that the performance improvement achieved by the super-lubricating coating technology in this application truly originates from the coating itself, rather than from interference from other factors, thus verifying the significant advancement and practical value of the technical solution presented in this application.
[0107] This application also provides a vertical axis wind turbine, which is manufactured using the manufacturing method of the vertical axis wind turbine described in the above embodiments.
[0108] The vertical axis wind turbine provided in this application includes: a base; a central main shaft vertically mounted on the base; a hub rotatably mounted on the central main shaft; multiple blades fixedly connected circumferentially to the hub; a bearing assembly disposed between the hub and the central main shaft; and a bracket fixed to the base. The surface of the bearing assembly is provided with a bearing super-lubricating coating, and the surface of the blades is provided with a blade super-lubricating coating. Specifically, the bearing super-lubricating coating is a composite lubricating coating comprising molybdenum disulfide, silica nanoparticles, and polyimide; the blade super-lubricating coating is a composite lubricating coating comprising molybdenum disulfide and silica. The outer surface of the blades is also provided with biomimetic microstructures, which are used to promote turbulent mixing within the boundary layer and form a multi-scale vortex field.
[0109] In this application, the bearing assembly is made of chromium-molybdenum-vanadium steel. The bearing assembly is machined and polished, with a surface roughness Ra ≤ 0.05 micrometers. This provides a high-quality adhesion substrate for the super-slippery coating, ensuring uniform coverage and strong adhesion of the coating. The blades are made of carbon fiber reinforced epoxy resin composite material. They are formed by autoclave process and their surface is polished to a mirror finish. They are lightweight, high-strength and have low surface roughness. Together with the super-slip coating, they further reduce air resistance.
[0110] Furthermore, the outer surface of the blade is equipped with biomimetic microstructures, such as sharkskin texture. These microstructures promote turbulent mixing within the boundary layer, creating a multi-scale vortex field on the blade surface and increasing the effective cross-sectional area, thereby further enhancing energy capture efficiency, especially under low wind speed conditions. The synergistic effect of drag reduction from the coating and vortex enhancement from the biomimetic microstructures optimizes the airflow path and significantly improves energy capture efficiency.
[0111] The bearing super-lubricating coating comprises molybdenum disulfide, silica nanoparticles, and polyimide. The layered, low-shear structure of molybdenum disulfide provides excellent lubrication, while the silica nanoparticles act as a hard filler to enhance the coating's hardness and wear resistance. Polyimide acts as a binder to ensure strong adhesion between the coating components and between the coating and the bearing substrate. Friction coefficient measurements verified that applying the super-lubricating coating reduced the bearing surface friction coefficient from 0.12 to 0.03, decreasing mechanical friction loss by approximately 75%.
[0112] The blade super-lubricating coating comprises molybdenum disulfide and silica. The low surface energy of molybdenum disulfide reduces the viscous drag between the blade surface and the airflow. Combined with silica nanoparticles that enhance the coating's density and hardness, this effectively reduces air resistance on the blade surface. Wind tunnel experiments have verified that, within a wind speed range of 5-15 m / s, the blade drag coefficient decreased from 0.45 to 0.30 after applying the super-lubricating coating, representing a reduction of approximately 33% in air resistance.
[0113] Long-term monitoring in actual wind farm environments shows that vertical axis wind turbines coated with super-slip coatings have an average power output increase of approximately 40%, especially under low wind speed (3-5 m / s) conditions, where power generation increases by 50%. Simultaneously, the super-slip coating reduces mechanical wear and enhances surface corrosion resistance, extending the service life of bearings and blades by approximately 30%, reducing maintenance frequency and costs, and improving the long-term stability of the system.
[0114] The vertical axis wind turbine provided in this application is particularly suitable for application scenarios with low wind speeds and complex turbulence, such as building surface installations in urban environments. It effectively solves the problem of low efficiency of traditional vertical axis wind turbines under low wind speed conditions and significantly improves energy conversion efficiency.
[0115] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
Claims
1. A method for manufacturing a vertical axis wind turbine, the vertical axis wind turbine comprising a bearing assembly and blades, characterized in that, The preparation method includes: S100. Pre-treat the surface of the substrate of the bearing assembly and prepare a bearing super-lubricating coating; S200: Pre-treat the surface of the substrate of the blade and prepare a super-slippery coating for the blade; S300. The bearing assembly with the super-lubricating coating and the blade with the super-lubricating coating are assembled into the vertical axis wind turbine. The bearing super-lubricating coating includes molybdenum disulfide as a base material, silica nanoparticles as nanofillers, and polyimide as a binder. S100 specifically includes: S110, sequentially cleaning and surface activation treatment of the substrate surface of the bearing assembly; S120, using chemical vapor deposition process to deposit the bearing super-lubricating coating on the substrate surface of the bearing assembly; The blade super-lubricating coating comprises molybdenum disulfide and silicon dioxide; S200 specifically includes: S210, sequentially cleaning and surface activation treatment of the substrate surface of the blade; S220, using physical vapor deposition process to deposit the blade super-slip coating on the substrate surface of the blade. S100 and S200 are performed independently and in parallel.
2. The method for manufacturing a vertical axis wind turbine according to claim 1, characterized in that, In step S120, the process conditions for the chemical vapor deposition process are as follows: Deposition temperature: 400℃; Chamber pressure: 10 - ³Torr; Flow rate of the precursor mixture of molybdenum disulfide and silicon dioxide: 20 sccm; Deposition time: 30 min-90 min; The thickness of the bearing super-lubricating coating is 50 nm-100 nm.
3. The method for manufacturing a vertical axis wind turbine according to claim 2, characterized in that, In step S120, the chemical vapor deposition process has a deposition time of 60 min and a bearing super-lubricating coating thickness of 50 nm.
4. The method for manufacturing a vertical axis wind turbine according to claim 1, characterized in that, Step S110 specifically includes: S111. Using an ultrasonic cleaner with anhydrous ethanol as solvent, the substrate surface of the bearing assembly is cleaned for 30 minutes at 40°C. S112. Using plasma treatment equipment, the surface of the substrate of the cleaned bearing assembly is activated in an oxygen atmosphere. The treatment power is 50W and the treatment time is 5min.
5. The method for manufacturing a vertical axis wind turbine according to claim 1, characterized in that, In step S220, the process conditions for the physical vapor deposition process are as follows: The deposition temperature was 150℃; The working gas is high-purity argon, and the pressure is maintained at 0.3 Pa. The sputtering power is 80W; The deposition time was 60 minutes. The thickness of the super-lubricating coating on the blade is 20 nm-40 nm.
6. The method for manufacturing a vertical axis wind turbine according to claim 5, characterized in that, In step S220, the thickness of the blade super-lubricating coating is 30 nm.
7. The method for manufacturing a vertical axis wind turbine according to claim 1, characterized in that, Step S210 specifically includes: S211. Using an ultrasonic cleaner with acetone as the solvent, clean the substrate surface of the blade at 30°C for 20 minutes. S212. Using ultraviolet light irradiation technology, the substrate surface of the cleaned blade is modified under nitrogen protection for 15 minutes.
8. The method for manufacturing a vertical axis wind turbine according to claim 1, characterized in that, Step S300 further includes: The bearing assembly coated with the super-slippery coating is installed between the hub and the central main shaft of the vertical axis wind turbine, and the bearing clearance is adjusted. The blades coated with the super-slippery coating are fixed to the hub circumferentially with high-strength bolts, and the blade angle is adjusted to the preset windward posture. After assembly, the vertical axis wind turbine is started to conduct no-load operation test and load operation test, and the power generation performance data is recorded.
9. A vertical axis wind turbine, characterized in that, The vertical axis wind turbine generator is manufactured using the method described in any one of claims 1-8, and includes a bearing assembly, blades, a support, and a base.
10. The vertical axis wind turbine generator according to claim 9, characterized in that, The bearing assembly is made of a high-performance metal alloy. The bearing assembly is machined and polished, and its surface roughness Ra ≤ 0.05 micrometers. The blade is made of carbon fiber reinforced epoxy resin composite material. The blade is formed by autoclave process, and its surface is polished to a mirror effect. The outer surface of the blade is provided with biomimetic microstructures.